Store Atmosphere, Price Discount and Purchasing Decisions of Shoe Stores in Bandar Lampung - Julia, Angelica; Roslina, Roslina; Nabila, Nuzul (Jurnal Ilmiah Manajemen Kesatuan, 2023)
This study investigates the influence of discounts and store atmosphere on purchasing decisions in shoe stores in Bandar Lampung, recognizing the evolving role of shoes from a basic foot protection necessity to a symbol of fashion. The purpose is to discern the impact of these factors on consumer behavior, particularly in a dynamic retail setting. The research, involving 100 respondents, employs purposive sampling to ensure representation of the population. Criteria for respondent selection include being over 17 years old and having made purchases in shoe stores. Data collection involves validated and reliable questionnaires, and SPSS version 26 is employed for statistical analysis, utilizing the multiple linear regression method. The results reveal that discounted prices and store atmosphere significantly influence purchasing decisions. These findings underscore the contemporary importance of factors beyond utilitarian aspects, shedding light on the interplay between economic considerations, retail strategies, and consumer preferences. Implications of this study extend to both marketers and consumers, guiding strategies for retailers to enhance the shopping experience and assisting consumers in making informed purchasing decisions in the evolving landscape of the fashion-centric shoe industry.